Learning without reading Noli me tangere the Rizal law in two public high schools - Aguilar, Filomeno V., Jr.; Macapagal, Ma. Elizabeth; Benitez, Christian Jil R. (2021)
The first to examine ethnographically the implementation of the 1956 Rizal Law, which mandated the inclusion of Jose Rizal's works in school curricula in the Philippines, this case study investigates the teaching of Noli me tangere at Grade 9 in two public high schools in Rizal Province. The data indicate that most students do not read the entire novel even in abridged form. But although many of them read summaries or assigned chapters only, they can articulate their learnings of life lessons and political values. This paradox is explained through classroom dynamics characterized by orality and formulaic learnings across teacher-student generations.
Keywords: Public education; Literature; Spanish colonial